FGFR Pathway Inhibition in Gastric Cancer: The Golden Era of an Old Target? - Csongor G. Lengyel; Sadaqat Hussain; Andreas Seeber; Sara Jamil Nidhamalddin; Dario Trapani; Baker S. Habeeb; Essam Elfaham; Syed Ayub Mazher; Fahmi Seid; Shah Z. Khan; Khalid El Bairi; Andrew Odhiambo; et al. (Life, 2022)
Gastric cancer (GC) is the third leading cause of cancer-associated death worldwide. The majority of patients are diagnosed at an advanced/metastatic stage of disease due to a lack of specific symptoms and lack of screening programs, especially in Western countries. Thus, despite the improvement in GC therapeutic opportunities, the survival is disappointing, and the definition of the optimal treatment is still an unmet need. Novel diagnostic techniques were developed in clinical trials in order to characterize the genetic profile of GCs and new potential molecular pathways, such as the Fibroblast Growth Factor Receptor (FGFR) pathway, were identified in order to improve patient’s survival by using target therapies. The aim of this review is to summarize the role and the impact of FGFR signaling in GC and to provide an overview regarding the potential effectiveness of anti-FGFR agents in GC treatment in the context of precision medicine.